Educational activity and tourism development in the landscape parks of Małopolska Voivodeship - Majewski, Karol; Zawilińska, Bernadetta (Turystyka i krajoznawstwo, 2021)
The article analyzes activity in the landscape parks of Małopolska Voivodeship in terms of education and tourism development. The empirical part of the article consists of two components: (1) analysis of the activities undertaken by the landscape parks, carried out on the basis of materials obtained from their joint management and interviews with its employees; (2) presentation of residents’, tourists’ and local authorities’ opinions on these activities collected through questionnaire surveys. Landscape parks conduct educational activity which is closely related to activities in the field of tourism development. These include conducting thematic classes - mainly taking place in schools and less often in the field, maintaining educational centers, educational trails and websites, as well as publishing materials. The functioning of landcape parks is supported both by local residents and tourists, although the parks as an institution are only poorly recognized. The high declared interest in participating in educational initiatives (especially in tours) and the support for local governments create favorable conditions for the development of Małopolska Voivodeship’s landscape park activity.